Clinicopathologic and genomic characterizations of brain metastases using a comprehensive genomic panel - Barakeh, Duna H.; Alsolme, Ebtehal; Alqubaishi, Fatimah; Almutairi, Amal; Alhabeeb, Lamees; Al Abdulmohsen, Sally; Almohsen, Shahd S.; Alayed, Doaa; AlAnazi, Sara Rashid; AlZahrani, Malak; Binowayn, Albandari Mohammed; AlOtaibi, Sarah S.; et al. (Frontiers in Medicine, 2022)
Central nervous system (CNS) metastasis is the most common brain tumor type in adults. Compared to their primary tumors, these metastases undergo a variety of genetic changes to be able to survive and thrive in the complex tissue microenvironment of the brain. In clinical settings, the majority of traditional chemotherapies have shown limited efficacy against CNS metastases. However, the discovery of potential driver mutations, and the development of drugs specifically targeting affected signaling pathways, could change the treatment landscape of CNS metastasis. Genetic studies of brain tumors have so far focused mainly on common cancers in western populations. In this study, we performed Next Generation Sequencing (NGS) on 50 pairs of primary tumors, including but not limited to colorectal, breast, renal and thyroid tumors, along with their brain metastatic tumor tissue counterparts, from three different local tertiary centers in Saudi Arabia. We identified potentially clinically relevant mutations in brain metastases that were not detected in corresponding primary tumors, including mutations in the PI3K, CDK, and MAPK pathways. These data highlight the differences between primary cancers and brain metastases and the importance of acquiring and analyzing brain metastatic samples for further clinical management.